Extirpation despite regulation? Environmental assessment and caribou. Issue 4 (14th March 2020) - Collard, Rosemary‐Claire; Dempsey, Jessica; Holmberg, Mollie
Abstract: Many caribou populations in Canada face extirpation despite dozens of provincial and federal legislative instruments designed to protect them. How are industrial developments that impact caribou justified and permitted despite governments' commitments to caribou protection? Toward an answer, this paper scrutinizes an approval process for major projects in Canada: environmental assessment (EA). We identify 65 EAs for major projects with potentially significant adverse impacts for caribou—all projects but one were approved. The results show that most projects were approved on the basis of proposed mitigation measures that promise to render adverse effects "insignificant"; yet mitigation effectiveness is largely unknown. Further, several projects were approved even though mitigation measures were insufficient, citing public or national interest. Finally, some projects' approval rested in part on scientific claims that the project area is already degraded or absent of caribou. Based on these findings, EA is failing caribou, acting as a means by which the state licenses major developments with potentially significant adverse effects for caribou, with a pretense of protection. The failure stems in part from a broader tension within the state that manifests in EA: a tension between the state's roles promoting economic growth and protecting against this growth's negative effects. Recognition of this tension needs to be more central to conservation biology. Abstract : Caribou on a pipeline in northeast BC. Photo credit: Land Use Department of West Moberly First Nations.